2019
DOI: 10.1016/j.jqsrt.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Chord length distribution in d-dimensional anisotropic Markov media

Abstract: Markov media are often used as a prototype model in the analysis of linear particle transport in disordered materials. For this class of stochastic geometries, it is assumed that the chord lengths must follow an exponential distribution, with a direction-dependent average if anisotropy effects are to be taken into account. The practical realizability of Markov media in arbitrary dimension has been a long-standing open question. In this work we show that Poisson hyperplane tessellations provide an explicit cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Quenched disorder models satisfying the Markov property for the chord lengths 6 were introduced by Pomraning and co-workers for one-dimensional geometries, based on a Poisson point process on the line [1]. We have recently shown that Markov media for any dimension d can be generated by using homogeneous Poisson tessellations, i.e., stochastic partitions of a domain into convex polyhedra obtained by homogeneously sampling hyperplanes, and then assigning each polyhedron of the tessellation a label α with probability p α [16,34]. For this purpose, we have developed a computer code that can construct such geometries by Monte Carlo methods, with arbitrary anisotropy laws [16,34]; examples of realizations for isotropic Poisson tessellations are provided in fig.…”
mentioning
confidence: 99%
“…Quenched disorder models satisfying the Markov property for the chord lengths 6 were introduced by Pomraning and co-workers for one-dimensional geometries, based on a Poisson point process on the line [1]. We have recently shown that Markov media for any dimension d can be generated by using homogeneous Poisson tessellations, i.e., stochastic partitions of a domain into convex polyhedra obtained by homogeneously sampling hyperplanes, and then assigning each polyhedron of the tessellation a label α with probability p α [16,34]. For this purpose, we have developed a computer code that can construct such geometries by Monte Carlo methods, with arbitrary anisotropy laws [16,34]; examples of realizations for isotropic Poisson tessellations are provided in fig.…”
mentioning
confidence: 99%